Ensuring the continuation of routine primary care during the COVID-19 pandemic: a review of the international literature. (6th October 2021) - Matenge, Sethunya; Sturgiss, Elizabeth; Desborough, Jane; Hall Dykgraaf, Sally; Dut, Garang; Kidd, Michael
Abstract: Background: The COVID-19 pandemic has resulted in the diversion of health resources away from routine primary care delivery. This disruption of health services has necessitated new approaches to providing care to ensure continuity. Objectives: To summarize changes to the provision of routine primary care services during the pandemic. Methods: Rapid literature review using PubMed/MEDLINE, SCOPUS, and Cochrane. Eligible studies were based in primary care and described practice-level changes in the provision of routine care in response to COVID-19. Relevant data addressing changes to routine primary care delivery, impact on primary care functions and challenges experienced in adjusting to new approaches to providing care, were obtained from included studies. A narrative summary was guided by Burns et al.'s framework for primary care provision in disasters. Results: Seventeen of 1, 699 identified papers were included. Studies reported on telehealth use and public health measures to maintain safe access to routine primary care, including providing COVID-19 screening, and establishing dedicated care pathways for non-COVID and COVID-related issues. Acute and urgent care were prioritized, causing disruptions to chronic disease management and preventive care. Challenges included telehealth use including disparities in access and practical difficulties in assessing patients, personal protective equipment shortages, and financial solvency of medical practices. Conclusions: Substantial disruptions to routine primary care occurred due to the COVID-19 pandemic. Primary care practices' rapid adaptation, often with limited resources and support, demonstrates agility and innovative capacity. Findings underscore the need for timely guidance and support from authorities to optimize the provision of comprehensive routine care during pandemics. Lay Summary: The COVID-19 pandemic has resulted in considerable disruption to health services including regular primary care. As a consequence, primary care practices have had to adopt new ways of providing care to ensure ongoing availability of services. However, little is known about the type of measures taken by care providers and challenges encountered in reorganizing services. The aim of this research was to provide a detailed understanding of changes in the way primary care was delivered and to identify difficulties experienced by patients and providers in adjusting to new approaches. The 17 studies included in the review indicate that primary care providers quickly put in place strategies including telehealth (e.g. telephone and video consultations) and infection control measures to ensure safe access to care. Furthermore, urgent and short-term care were prioritized resulting in interruptions to other services, including management of preexisting or long-term illnesses. Challenges included barriers to accessing telehealth such as inadequate internet connection and practical difficulties in examining patients, personal protective equipment shortages, and financial losses by practices. Adequate support from authorities is needed to enhance the provision of comprehensive primary care during pandemics.